Substantiation of the Program for Prevention of Dental Diseases in Able-Bodied Women with the Diagnosis or Regular Miscarriage - E.A. , Vartanian; O.V. , Gridnev; E.V. , Pesennikova; L.L. , Naumenko (International Journal of Psychosocial Rehabilitation, 2020)
Diagnosis of extragenital diseases is of great importance in studying the mechanism of development of the pathology of oral tissue during pregnancy, since the dental health of the unborn child also depends on the level of health of the pregnant woman. Considering the above, the aim of the work was to substantiate the development of a program for the prevention of dental diseases in able-bodied women with a diagnosis of regular miscarriage. The object of the study was outpatient records and medical history (a total of 2017 records of pregnant women). To study the predictors of dental morbidity, an experimental group of pregnant women was formed (31 persons). Factors affecting the intensity of dental diseases in the examined group of pregnant women, namely, the age group (p = 0.032), presence of children (p = 0.004), and the presence of periodontal pockets (p = 0.006), were revealed. As a result of the work, risk factors for the development of dental pathology were established, and a program for the prevention of dental diseases during pregnancy in women with regular miscarriage was substantiated, which supposed continuity in the work of dental medical organizations serving pregnant women, antenatal clinics, and specialists.